Theoretical backgrounds of learning at different levels of difficulty in learning and teaching - Gaxhiqi, Behxhet (Technium Social Sciences Journal, 2023)
Firstly, in the determination of this paper, it is very important to note that so far nothing has been done in this regard, as it is known that a large number of different factors have been influenced. By defining this paper we will explore and illuminate the factors but also the stagnation that directly affects learning and teaching.Also, this paper will analyze the possibilities for implementing and applying an advanced learning format that directly affects this content learnable lessons comprehension by students, in our schools.We will continue to recognize those factors that are effective and have impacted on this area of learning.Students with such problems have a variety of difficulties, focusing on attention, having difficulties in performing tasks and passing quickly from one activity to another etc.These learners also show other behaviors such as: they are often confused, forget things, do not care, do not repeat, develop excessive conversations, or move often in the classroom etc.In addition paper also has analyzed the theoretical and practical aspect of students in learning and teaching.